A call to action from the Purdue University Center for Health Equity and Innovation. Issue 8 (9th June 2022) - Gonzalvo, Jasmine D.; Meredith, Ashley; Adeoye‐Olatunde, Omolola; Kimiecik, Carlyn; Pastakia, Sonak; Rodriguez, Natalia; Ruiz, Yumary; Ott, Carol; Schellhase, Ellen; Crawford, Elizabeth; Crowe, Susie; Samuel, Jeffrey; et al.
Abstract: The Purdue University College of Pharmacy established the Center for Health Equity and Innovation (CHEqI) to provide students, faculty, and internal and external partners with a coordinating center whose primary purpose is to address inequities in the social determinants of health. Through this article the development of the center, the interdisciplinary activities the center is currently engaged in, ongoing educational efforts to provide instruction related to equity, and research endeavors designed to better understand the impact of our efforts are described. Pharmacists and colleges/schools of pharmacy must optimize health equity efforts with interdisciplinary partners by: (1) providing student opportunities to learn about diverse populations through engagement and integration with communities, (2) encouraging students to identify and lead health equity initiatives, (3) incorporating health equity engagement and track impact of efforts designed to address inequity into annual review and promotion processes, (4) creating and participating in health equity training opportunities, and (5) developing a formal structure for collaborative networks to align health equity efforts. These five strategies and examples are not intended to be prescriptive, but rather, an opportunity to synergize and cultivate further discussion of work in health equity across colleges/schools of pharmacy.